Damaged by the Disaster : The Impact of COVID-19 on Firms in South Asia - Brucal, Arlan; Grover, Arti; Reyes Ortega, Santiago (World Bank, Washington, DC, 2021)
To assess the impact of COVID-19 on firms, the World Bank and the International Finance Corporation conducted Business Pulse Surveys in several countries, including six in the South Asia region. Analysis focusing on the South Asia region suggests that, first, firms in the South Asia region have suffered disproportionately more from the economic brunt of the pandemic. Second, even within the region, COVID-19 did not affect all firms equally. Although exporters remain resilient by some metrics, firms that are smaller, female-led firms and those in vulnerable sectors suffered higher rates of closure. Third, while digital technologies have taken the center stage post-pandemic, the South Asia region lags in the adoption of these technologies. Finally, policy support for firms is key to building back better and resilient recovery, yet only a small share of firms can access public support. To be effective, firm support programs ought to be carefully customized and target firms based on the dominant channel through which COVID-19 affects them rather than their external attributes.